Social dominance orientation underlies social valuation in a competitive social hierarchy - Qiang, Zhang; Haruno, Masahiko (Frontiers in Psychology, 2025)
IntroductionHumans are constantly evaluating whether they are in a fair situation. However, perceptions of fairness vary widely across individuals. What governs this individual variability in fairness perception remains poorly understood. In this study, we hypothesized that individual sensitivity to social dominance hierarchies influences fairness perception and therefore tested whether social dominance orientation (SDO) accounts for such individual preferences.MethodWe first assessed SDO scores in 29 participants using a standard SDO questionnaire. Participants then completed two competitive tasks. In the first task, they engaged in repeated competitions to establish a social hierarchy among opponents. In the second (main) task, participants played against opponents whose ranks were determined in the first task. Each trial in the second task awarded both a performance-based reward and a variable bonus (independent of win/loss) to both the participant and their opponent. Participants rated the desirability (social valuation) of each bonus distribution on a 4-point scale (1 = least preferable, 4 = most preferable). Using LASSO regression, we examined how self-reward, bonus inequity, outcomes (win/loss), opponent rank, SDO, and their interactions affected social valuation.ResultWe found that the outcome modulated the influence of bonus inequity on social valuation, with inequity having a stronger effect on win trials. Crucially, low-SDO individuals tended to favor larger bonuses for winners in loss trials, whereas high-SDO individuals consistently preferred larger bonuses for themselves regardless of the outcome. Moreover, high-SDO participants rated bonuses more favorably when facing lower-ranked opponents, while low-SDO individuals showed the opposite pattern.DiscussionThese findings suggest that SDO, interacting with the competitive outcome, plays a key role in shaping dynamic social valuation.